2016
DOI: 10.1136/bmj.i5210
|View full text |Cite
|
Sign up to set email alerts
|

Health consequences of shift work and insufficient sleep

Abstract: This review summarises the literature on shift work and its relation to insufficient sleep, chronic diseases, and accidents. It is based on 38 meta-analyses and 24 systematic reviews, with additional narrative reviews and articles used for outlining possible mechanisms by which shift work may cause accidents and adverse health. Evidence shows that the effect of shift work on sleep mainly concerns acute sleep loss in connection with night shifts and early morning shifts. A link also exists between shift work an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
681
3
12

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 800 publications
(708 citation statements)
references
References 133 publications
12
681
3
12
Order By: Relevance
“…When persons are affected by sleepiness or fatigue, their attention and decision-making abilities during work activities, on the road or in relation to home or leisure-time activities, can become seriously weakened. However, the evidence of a causal pathway from shift work through sleepiness to accidental injuries remains unestablished due to limited epidemiological support [reviewed in (18)]. …”
mentioning
confidence: 99%
“…When persons are affected by sleepiness or fatigue, their attention and decision-making abilities during work activities, on the road or in relation to home or leisure-time activities, can become seriously weakened. However, the evidence of a causal pathway from shift work through sleepiness to accidental injuries remains unestablished due to limited epidemiological support [reviewed in (18)]. …”
mentioning
confidence: 99%
“…Studies have in fact consistently shown that sleep loss, resulting for example from shift-working schedules, is associated with increased risk of accidents and, in the long-term, even health consequences such as type-2 diabetes and cancer [25]. Furthermore, when recurrent sleep loss is not followed by adequate sleep recovery, it can lead to increased risk of infections as well as chronic conditions [26].…”
Section: Resultsmentioning
confidence: 99%
“…This disruption may be temporary, as occurs with travel between time zones ‘jetlag’ or with society-wide changes to wake times via daylight savings time, or more permanent as with ongoing shift work. Night shift work, in particular, may result in profound circadian misalignment and many studies on shift workers have demonstrated the negative influence this can have on health 25. A milder, yet chronic, form of circadian misalignment is social jetlag (SJL).…”
Section: Introductionmentioning
confidence: 99%